ANALYSIS OF UROLOGICAL MORBIDITY IN THE ADULT POPULATION MOSCOW FOR THE YEARS 2006-2015 - Геворкян, Ашот Рафаэлович (Medicine in Kuzbass, 2017)
The article, based on the materials of the official statistical reporting for 2006-2015, analyzed the trends of the urological diseases of the adult population of Moscow, compared with the Russian Federation. It is established, diseases of the genitourinary system (GUS) consistently occupy the third place in the structure incidence and fourth place in the adult morbidity structure of the population of Moscow and the Russian Federation. In2015, inMoscow, their share was 7,6 % among new cases of disease and 8,7 % of all diseases registered among the adult population. Primary morbidity disease GUS adult population of Moscow, according to the analysis of statistical reports ambulatory polyclinic institution (API), decreased in 2015 compared to 2006 by 33,7 %, kidney and ureter disease – by 16,3 %, prostate disease – by 48,7 %. However, this trend in the incidence of urinary tract does not match the results of special epidemiological studies and may be due to underreporting of these diseases and the low level of diagnosis. Revealed significant deficiencies in the organization of follow-up of patients with urological diseases in Moscow. In 2015, medical observation covered only 26,6 % of patients with kidney and ureter, 21,1 % of all patients with urolithiasis, 23,6 % – with prostate disease, 12,9 % – with male infertility. It was established that further modernization of statistical urological diseases as valid statistical form (f N 12) offers limited possibilities for the analysis of the incidence and prevalence of urological diseases in the context of individual clinical entities.